Marine snow formation in the aftermath of the Deepwater Horizon oil spill in the Gulf of Mexico - U Passow; K Ziervogel; V Asper; A Diercks (Environmental Research Letters, 2012)
The large marine snow formation event observed in oil-contaminated surface waters of the Gulf of Mexico (GoM) after the Deepwater Horizon accident possibly played a key role in the fate of the surface oil. We characterized the unusually large and mucus-rich marine snow that formed and conducted roller table experiments to investigate their formation mechanisms. Once marine snow lost its buoyancy, its sinking velocity, porosity and excess density were then similar to those of diatom or miscellaneous aggregates. The hydrated density of the component particles of the marine snow from the GoM was remarkably variable, suggesting a wide variety of component types. Our experiments suggest that the marine snow appearing at the surface after the oil spill was formed through the interaction of three mechanisms: (1) production of mucous webs through the activities of bacterial oil-degraders associated with the floating oil layer; (2) production of oily particulate matter through interactions of oil components with suspended matter and their coagulation; and (3) coagulation of phytoplankton with oil droplets incorporated into aggregates. Marine snow formed in some, but not all, experiments with water from the subsurface plume of dissolved hydrocarbons, emphasizing the complexity of the conditions leading to the formation of marine snow in oil-contaminated seawater at depth.